2009
DOI: 10.1111/j.1465-3362.2009.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor criterion validity of self‐reported hepatitis B infection and vaccination status among injecting drug users: A review

Abstract: Self-reported histories should not be used in lieu of serological testing when assessing infection history or immunisation status. Poor criterion validity also indicates that self-reports of HBV infection status should not be used to estimate the prevalence and incidence of this infection. Due to their low sensitivity, self-reports of HBV infection should at best be considered only as a lower bound prevalence estimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…Previous studies have reported different results regarding the reliability of self-reported vaccination history. Some suggested that self-reported vaccination history and personal information are reliable in that they are consistent with the health information documented in medical records [28,29] but a study have found opposite results [30]. Information bias may have led to inaccurate information about vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported different results regarding the reliability of self-reported vaccination history. Some suggested that self-reported vaccination history and personal information are reliable in that they are consistent with the health information documented in medical records [28,29] but a study have found opposite results [30]. Information bias may have led to inaccurate information about vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…However, knowing which individuals to vaccinate is complicated by the possibility that they could have already been vaccinated for both hepatitis A and B, either during infancy or childhood depending on their U.S. state of residence and date of birth, or due to their risk behaviors [11][12][13][14]. One way to determine vaccination status of individual PWID is to ask them if they've been vaccinated; however, studies on self-report of hepatitis B vaccination in PWID show poor prediction of actual serologic status, either because their memory of what vaccines they received in childhood is poor and they lack documentation of childhood vaccinations or their titers waned over time [17]. Limited studies examining self-report of hepatitis A vaccine among PWID are available.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of an effective three‐dose HBV vaccine since 1982, coverage among PWID is low, leaving them vulnerable to infection . Many Australian PWID are unaware of the availability of hepatitis B tests or vaccination and around half do not know their true HBV status . Several studies have also identified multiple missed opportunities for vaccination during contact with prisons, drug treatment centers or other primary or tertiary health centers …”
Section: Introductionmentioning
confidence: 99%